2012
DOI: 10.1186/1471-2148-12-236
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of ultraconserved elements with different phylogenetic origins

Abstract: BackgroundUltraconserved elements of DNA have been identified in vertebrate and invertebrate genomes. These elements have been found to have diverse functions, including enhancer activities in developmental processes. The evolutionary origins and functional roles of these elements in cellular systems, however, have not yet been determined.ResultsHere, we identified a wide range of ultraconserved elements common to distant species, from primitive aquatic organisms to terrestrial species with complicated body sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 61 publications
(91 reference statements)
3
22
0
Order By: Relevance
“…To examine the intrinsic biological roles of the conserved regions, we queried the 50 most overrepresented heptamer against FlyReg motifs [23] using STAMP [24] and detected many putative TF binding sites (TFBSs) related to developmental TFs ( Figure 1C and Table S2 ). This result is consistent with previous reports showing that HCNEs harbor binding sites for developmental TFs [3] , [25] .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…To examine the intrinsic biological roles of the conserved regions, we queried the 50 most overrepresented heptamer against FlyReg motifs [23] using STAMP [24] and detected many putative TF binding sites (TFBSs) related to developmental TFs ( Figure 1C and Table S2 ). This result is consistent with previous reports showing that HCNEs harbor binding sites for developmental TFs [3] , [25] .…”
Section: Resultssupporting
confidence: 94%
“…Coding sequences are generally under higher selective pressure than noncoding sequences, due to the essential roles that proteins play in the cell [1] . However, some noncoding regions show extreme conservation (even more than coding sequences) over very long evolutionary timeframes [2] , [3] . These extremely conserved sequences are found universally in multicellular eukaryotes of the animal and plant kingdoms [3] , [4] , indicating that such sequences have essential functions.…”
Section: Introductionmentioning
confidence: 99%
“…Although their complete functional characterization is still a long way off, it is known that UCEs are not randomly distributed, and their position within the genome also seems to reflect their function. These constrained sequences are in fact mostly allocated in clusters, flanking, or embedding genes involved in important physiological processes, and act as splicing or enhancer factors [ 92 ]. Their extreme conservation could be due to the absence of annotated transposons near many UCEs during evolution [ 93 ].…”
Section: Ultraconserved Elements (Uces): a Close Look At Evolutionarymentioning
confidence: 99%
“…None of the 481 UCEs identified by Bejerano and co-authors [7] overlap with the UCEs identified between phylogenetically distant species such as human and demosponge, hydra or sea anemone [9]. However, a recent study has described 183 CNEs conserved between mammals, fishes and tunicates, of which 145 overlap with an extended set of 5,404 vertebrate UCEs [37].…”
Section: Introductionmentioning
confidence: 99%